2001
DOI: 10.1021/jp012636y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of a Double-Decker Lutetium(III) Phthalocyanine in Aqueous Media. The First Evidence for Five Reductions

Abstract: The double-decker lutetium(III) phthalocyanine, Lu[(RS)4Pc]2, where R = C12H25, was synthesized and electrochemically characterized under several solution conditions. The neutral complex undergoes a single reversible one-electron oxidation and up to four reversible one-electron reductions in nonaqueous solutions of CH2Cl2 or benzonitrile containing 0.1 M tetra-n-butylammonium perchlorate (TBAP), while one oxidation and five reductions are seen in aqueous 0.5 M KCl for a gel-like cast film membrane of Lu[(RS)4P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…14 The resulting high degree of charge carrier mobility readily explains their semiconductivity 15,16 and electrochromic behavior. 17,18 In its electronic ground state, lutetium bisphthalocyanine ([LuPc 2 ]) is a stable radical ([LuPc 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…14 The resulting high degree of charge carrier mobility readily explains their semiconductivity 15,16 and electrochromic behavior. 17,18 In its electronic ground state, lutetium bisphthalocyanine ([LuPc 2 ]) is a stable radical ([LuPc 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…[12b,15] The same methodology has been applied here to render possible the first observation by DPV of the fifth one-electron reduction of M(Pc) 2 in solution. [15] Results and Discussion The electrochemical behavior of all the double-decker sandwich complexes M(Pc) 2 was first investigated by cyclic voltammetry (CV) and then differential pulse voltammetry (DPV) in CH 2 Cl 2 . The half-wave redox potentials vs. SCE are summarized in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Direct proportionality of the cathodic peak current with the scan rate provides evidence for the adsorption character of reduction wave [31]. The anodic or cathodic peak potentials of the complexes could be expected to shift by the introduction of electron-donating or electron-withdrawing groups on the oxime moity as previously observed for phthlocyanine complexes [32][33][34][35][36]. However, the experimental results showed that no introduction of the electron-donating phenyl groups on the oxime moity for [Ni(L 2 H) 2 …”
Section: Magnetic Momentsmentioning
confidence: 85%